2006
DOI: 10.1385/bter:110:1:19
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Dose Sodium Selenite Therapy on Polymorphonuclear Leukocyte Apoptosisin Non-Hodgkin's Lymphoma Patients

Abstract: The present study was undertaken to explore the effect of the administration of high doses of sodium selenite on apoptosis in polymorphonuclear leukocytes in patients with non-Hodgkin's lymphoma. Thirty patients with newly diagnosed non-Hodgkin's lymphoma were randomly divided into two groups. Group I was treated with chemotherapy and group II received 0.2 mg/kg/d sodium selenite in addition to chemotherapy. Flow cytometry was used for the monitoring of apoptosis on peripheral blood neutrophils at the time of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 17 publications
0
16
0
1
Order By: Relevance
“…Selenium is an essential trace element with the potential chemopreventive effects against various cancers (6)(7)(8)(9). Our previous work has shown that 20 ÎŒM sodium selenite can induce apoptosis in NB4 cells (10).…”
Section: Introductionmentioning
confidence: 99%
“…Selenium is an essential trace element with the potential chemopreventive effects against various cancers (6)(7)(8)(9). Our previous work has shown that 20 ÎŒM sodium selenite can induce apoptosis in NB4 cells (10).…”
Section: Introductionmentioning
confidence: 99%
“…A small clinical randomized study in patients with non-Hodgkin's lymphoma showed that Se supplementation during chemotherapy increases the percentage of cases with a reduction of lymphadenopathy, and decreases splenic size and bone marrow infiltration [15]. Further prospective clinical trials showed that Se can reduce toxicities of chemotherapy in patients with solid tumors and hematological malignancies [15,16,17,18,19,20]. …”
mentioning
confidence: 99%
“…Asfour et al (2006) demonstrated that the sodium selenite administration to humans with non-Hodgkin's lymphoma and treated by chemotherapy resulted in a signiϐicant reduction in neutrophils apoptosis compared to those who were not supplemented with sodium selenite. The viable neutrophils (nonapoptotic) markedly improved the overall post therapy neutropenic phase and decreased signiϐican-tly possible life threatening infections.…”
Section: Resultsmentioning
confidence: 99%